La habilidad de clasificación y el juego para la comprensión del número hasta 9, en 1° grado de Educación Primaria - Cienfuegos Chavez, Maria Elena (2021)
The present work of Professional Sufficiency aims to explain how to stimulate the classification ability and the game, they contribute to the understanding of the number up to 9 in first grade of primary education. The explanation is done through the planning, implementation of a learning session and the theoretical and pedagogical support, based on my professional experience as a classroom teacher with 1st grade children.